Three new species, one new record and an updated checklist of Begonia (Begoniaceae) from Kalimantan, Indonesia - Randi, Agusti; Ardi, Wisnu H.; Girmansyah, Deden; Sitepu, Bina Swasta; Hughes, Mark (Phytotaxa, 2022)
Three new Begonia species from Kalimantan, Indonesian Borneo are described here, namely Begonia kapuashuluensis, B. patar and B. sangkulirangensis, and one species is reported as a new record for Kalimantan. Colour plates, as well as notes on distribution, habitat and conservation status are provided. On conservation status, we provisionally assess B. kapuashuluensis as near threatened, B. patar as critically endangered and B. sangkulirangensis as vulnerable.